Hydrocarbon Source Rock Potential and Thermal Maturity of Baong, Peutu, and Bampo Formations in the North Sumatra Basin, Indonesia - Adrian, Fahri; Syah Putra, Hidayat; Sartika, Dewi; Rifqan; Fajrin, Haffiza (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
This study investigates the hydrocarbon source rock potential and thermal maturity of shale and mudstone outcrop samples from the Baong, Peutu, and Bampo Formations in the North Sumatra Basin, Indonesia. These fine-grained, calcareous, organic-rich, and low-permeability rocks are widely recognized as potential hydrocarbon source rocks. Source rocks generate hydrocarbons through thermal maturation processes, and their effectiveness is primarily controlled by organic richness, kerogen type, and thermal maturity. A total of six (6) outcrop samples were collected and analyzed using Rock-Eval Pyrolysis and Vitrinite Reflectance methods to evaluate their geochemical characteristics. The Baong Formation samples show very good organic richness, with Total Organic Carbon (TOC) values ranging from 2.2 to 2.5%, and are dominated by Type II/III kerogen, indicating potential for mixed oil and gas generation. Tmax values of 428–429°C suggest that these samples are thermally immature. The Peutu Formation samples exhibit very good source rock potential, with TOC values of 3.3–3.8% and predominantly Type II/III kerogen, suitable for mixed oil and gas generation. Tmax values indicate thermal immaturity to early maturity. In contrast, the Bampo Formation samples are thermally mature but display poor organic richness (TOC < 0.5%) and low Hydrogen Index values, suggesting limited hydrocarbon generation potential dominated by Type III kerogen. Although interpretations are based on outcrop samples, the results provide important implications for evaluating the petroleum system of the North Sumatra Basin, particularly in understanding source rock distribution, quality, and maturity trends.